IgG4‐Related Disease Mimicking Metastatic Malignancy: Polyserositis and Abdominal Lymphadenopathy - Meisi Huo; Jinhua Li; Shuqi Wu; Shiyan Yan (Clinical Case Reports)
ABSTRACT In patients presenting with multiple space‐occupying lesions, preserved general condition, and normal or mildly elevated tumor markers, IgG4‐related disease (IgG4‐RD) should be considered in the differential diagnosis. We report an extremely unusual case of IgG4‐RD mimicking metastatic malignancy, with polyserositis and widespread abdominal lymphadenopathy.